Desain dan Implementasi Mesin Penggiling Singkong untuk Peningkatan Produktivitas UMKM Kerupuk Bu Ita di Kabupaten Lima Puluh Kota: Design and Implementation of a Cassava Grinding Machine to Improve the Productivity of UMKM Kerupuk Bu Ita in Lima Puluh Kota Regency, West Sumatra - Taufik Taufik; Elita Amrina; Alizar Hasan; Nilda Tri Putri; Hilma Raimona Zadry; Ahmad Syafruddin Indrapriyatna; Eri Wirdianto; Insannul Kamil; Prima Fithri; Wisnel Wisnel; Dina Rahmayanti; Desto Jumeno; Reinny Patrisina; Alexie Herryandie Bronto Adi; Ashila Nurul Huda; Rahmad Inca Liperda; Firdruzal Fahlevi; Hary Fandel; Ghufran Maulana (LPPM Universitas Andalas, 2026)
Small and medium food enterprises in Indonesia continue to face challenges in adopting appropriate processing technologies, particularly in cassava-based production, which limits efficiency, productivity, and product quality consistency. This study aims to design and implement a food-grade cassava grinding machine as a technological intervention to increase production capacity at the Kerupuk Bu Ita enterprise in Padang. The research applied a Research and Development (R&D) approach using the Define–Design–Develop–Evaluate–Disseminate model with participatory involvement of the target users. The machine was tested through performance measurement, time efficiency analysis, and ergonomic assessment. The results indicate a substantial improvement compared to the manual process, where grinding capacity increased from 10–13 kg/hour to 70–80 kg/hour, representing a productivity enhancement of 450–580%, while processing duration was reduced from approximately 3 hours to about 1 hour, resulting in a 66% reduction in processing time. In addition, user evaluation shows that the machine is easier to operate and ergonomically more suitable for continuous use. These findings demonstrate that the developed cassava grinding machine significantly improves production performance and offers a practical solution for strengthening the competitiveness of SMEs. The study contributes scientifically by providing a validated prototype of appropriate technology tailored to the operational and ergonomic needs of small-scale food production units.